SAFETY PRACTICES OF INDUSTRIES IN THREE AREAS OF SPECIALTIES IN TECHNICAL EDUCATION (NAU Journal of Technology and Vocational Education, 2024)
This study appraised the safety practices of industries in the three out of the six majorareas of Technical Education, which span across building, mechanical, and electricaltechnology industries. Two research questions and two null hypotheses, tested at 0.05level of significance guided the study. A 15-item questionnaire, meant to ascertain thesafety practices in the workplace was administered to 30 factory workers in the threeindustries in three areas of technical education. The instrument which was validatedby experts, yielded a reliability coefficient of 0.87. Mean was used to analyze data toanswer the research questions, while Analysis of Variance (ANOVA) was employedto test the hypotheses. Findings showed that the prevalence of accident in industries isnot because of absence of safety equipment, but a combination of careless attitude ofworkers, and employers’ failure to enforce compliance to safety rules. The study alsorevealed that safety practices in an industry does not depend on the type of work itengages in. The findings have implications for technical education practitioners.Amongst others, it was recommended that industries should provide adequatemeasures to safeguard the health of workers.
Keywords: Safety Practices, Industries, Technical Education